2007
DOI: 10.1080/00016340600753117
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interruption of pelvic nerve pathways in dysmenorrhea: a systematic review of effectiveness

Abstract: The evidence for nerve interruption in the management of dysmenorrhea is limited. Methodologically sound and sufficiently powered randomized controlled trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
(55 reference statements)
0
23
0
2
Order By: Relevance
“…However, it is important to inform patients that endometriosis recurs within 2 years post laparoscopy in 40% to 60% of cases, and complications develop in 1% to 6% of cases (Winkel, 2003). Another surgical procedure, presacral neurectomy, which entails division of the sympathetic nerves from the uterus, may help reduce endometriosis-associated dysmenorrhea and midline abdominal pain (Latthe, Proctor, Farquhar, Johnson, & Khan, 2007). If pain symptoms continue to persist after attempting medical and surgical management, or side effects from medical therapy become intolerable, definitive surgery, which includes hysterectomy with bilateral salpingectomy and oophorectomy, may be considered as a final treatment option in patients with no plans for pregnancy (Jackson & Telner, 2006;Mounsey et al, 2006).…”
Section: Managementmentioning
confidence: 99%
“…However, it is important to inform patients that endometriosis recurs within 2 years post laparoscopy in 40% to 60% of cases, and complications develop in 1% to 6% of cases (Winkel, 2003). Another surgical procedure, presacral neurectomy, which entails division of the sympathetic nerves from the uterus, may help reduce endometriosis-associated dysmenorrhea and midline abdominal pain (Latthe, Proctor, Farquhar, Johnson, & Khan, 2007). If pain symptoms continue to persist after attempting medical and surgical management, or side effects from medical therapy become intolerable, definitive surgery, which includes hysterectomy with bilateral salpingectomy and oophorectomy, may be considered as a final treatment option in patients with no plans for pregnancy (Jackson & Telner, 2006;Mounsey et al, 2006).…”
Section: Managementmentioning
confidence: 99%
“…Several reports found no difference in symptoms at 3 years after surgery between the women who underwent laparoscopy alone and the women who underwent laparoscopy with UNA [24,25]. Several authors reported modest clinical benefits of UNA [26,27]. By contrast, many studies, including randomized trials, showed that presacral neurectomy (PSN) significantly improved symptoms [25,27,28]…”
Section: Treatment Of Endometriosis-associated Painmentioning
confidence: 93%
“…Laparotomy or laparoscopy plus presacral neurectomy has better results than surgery only in regard to: recurrence of dysmenorrhea at 1-year follow-up (17% and 25%, respectively), dysmenorrhea relief at 6 and 12 month follow-up (87% vs 60%, and 86% vs 57%, respectively), severity of dysmenorrhea, dyspareunia, non-menstrual pelvic pain and health-related quality of life at 24-month follow-up (Zullo et al, 2004). However, this technique presents limitations that must be taken into account: first, it is effective in reducing midline pain only, whereas lateral, adnexal pain is not influenced; second, denervation of bowel and bladder cause de-novo constipation (15%) and urinary urgency (5%) (Latthe et al, 2007;Zullo et al, 2004); third, great care must be taken to avoid damaging the right ureter and major and midsacral vessels (Berlanda et al, 2010). Systematic performance of presacral neurectomy cannot be recommended, only in patients with central, hipo-gastric pain (Latthe et al, 2007;Vercellini et al, 2009).…”
Section: Pelvic Denervating Proceduresmentioning
confidence: 99%
“…The addition of uterosacral ligament resection (i.e., laparoscopic uterosacral nerve ablation) to laparoscopic surgical treatment of endometriosis was not associated with a significant difference in any pain outcomes (Latthe et al, 2007).…”
Section: Pelvic Denervating Proceduresmentioning
confidence: 99%
See 1 more Smart Citation